Delayed gastric emptying and altered antrum protein metabolism during activity‐based anorexia. Issue 7 (6th February 2018) - Nobis, S.; Morin, A.; Achamrah, N.; Belmonte, L.; Legrand, R.; Chan, P.; do Rego, J.‐L.; Vaudry, D.; Gourcerol, G.; Déchelotte, P.; Goichon, A.; Coëffier, M.
Abstract: Background: Anorexia nervosa, a restrictive eating disorder, is often associated with gastrointestinal disorders, particularly a delayed gastric emptying. However, the mechanisms remained poorly documented. Thus, we aimed to evaluate gastric emptying and antrum protein metabolism in the Activity‐Based Anorexia model (ABA). Methods: Females C57Bl/6 mice were randomized into 3 groups: Control, ABA, and Limited Food Access (LFA). Food access has been progressively limited from 6 h/day at day 6 to 3 h/day at day 9 and until day 17. ABA mice had free access to an activity wheel. Gastric emptying was assessed. On gastric extracts, a proteomic analysis was performed, as well as an evaluation of protein synthesis and protein oxidation. Key Results: Both LFA and ABA mice exhibited a delayed gastric emptying compared with Controls ( P < .05). Proteomic approach revealed 15 proteins that were differentially expressed. Among these proteins, we identified 2 clusters of interest contributing to (i) the organization of muscle fiber with ACTA2, VCL, KRT19, KRT8, and DES proteins and (ii) "heat shock proteins" with STIP1, HSPD1, and HSPA8 proteins. ABA mice specifically exhibited an increased rate of gastric oxidized proteins. Conclusions and Inferences: Delayed gastric emptying observed in anorectic conditions appears to be secondary to malnutrition. However, an oxidative stress is specifically present in the stomach of ABA mice. Its role remains to be further studied. Abstract : We provide evidence of delayed gastric emptying in mice during activity‐based anorexia that was mainly due to malnutrition. We also evaluate the gastric proteome to better understand the underlying mechanisms.